ANALISIS PERBANDINGAN KEUNGGULAN KOMPETITIF DAN KOMPARATIF USAHATANI KEDELAI DAN PADI DI KABUPATEN GROBOGAN - Saputra, Irvan Aji; Simamora, Liska; Yuliawati, Yuliawati (Jurnal AGRISEP, 2021)
Grobogan District is a central of Soybeans and rice productions in Central Java. The purpose of this research is to know the value of a competitive, comparative, the financial and economic advantage of the soybeans and rice in Grobogan district. the study was conducted through by interviewing with 32 farms of soybeans and rice farmers as selected responders using purposive sampling techniques, namely farmers who planted soybeans and rice in the 2019/2020 planting season. The data analysis is used the Policy Analysis Matrix table (PAM). The result shows that both of the competitive and cooperative advantage of PCR result a pointed 0.30 and 0.28 with the DRCR score 0.44 and 0.14, the score is <1. Soybeans and rice farming in Grobogan district have a financial advantages around IDR 6.337.411/ha and IDR 14.713.109/ha, with ecomonic benefits of IDR 5.18.606/ha and IDR 33.698.996/ha.